1998
DOI: 10.1021/jp980262b
|View full text |Cite
|
Sign up to set email alerts
|

Physics of Nickel Clusters. 2. Electronic Structure and Magnetic Properties

Abstract: Using a combination of classical molecular dynamics simulation and first principles molecular orbital theory, we provide the first comprehensive study of the equilibrium geometries, energetics, electronic structure, vertical ionization potential, and magnetic properties of Ni clusters containing up to 21 atoms. The molecular dynamics simulation makes use of a tight binding many-body potential, while the calculations based on molecular orbital theory are carried out self-consistently using the numerical atomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
69
2
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(100 citation statements)
references
References 46 publications
28
69
2
1
Order By: Relevance
“…Khanna et al modelled the magnetic moment of clusters using a Langevin function where they predicted that the moment rose as n → 2 however there were variations in the moment due to different geometries causing different surface areas for each value of n. Khanna et al also comment on other predictions of the calculations of magnetic moment carried out by other groups stating that discrepancies may arise if the atomic spacing is considered to be similar to the bulk metal as the clusters moment will be sensitive to the local geometry and exchange distances. Khanna and Reuse used the local density approximation to calculate that for, Ni 3 , the moment per atom will equal 0.6 µ B and for Ni 5 , 1.6 µ B which is close to an experimental result of 1.8 µ B obtained by Reddy et al [20] and Reuse and Khanna [22] . Khanna et al have also reported that the electronic structure shows band-like behaviour at n = 14 suggesting a similarity to bulk behaviour which is radically different to prior experimental data.…”
Section: Introductionsupporting
confidence: 77%
See 3 more Smart Citations
“…Khanna et al modelled the magnetic moment of clusters using a Langevin function where they predicted that the moment rose as n → 2 however there were variations in the moment due to different geometries causing different surface areas for each value of n. Khanna et al also comment on other predictions of the calculations of magnetic moment carried out by other groups stating that discrepancies may arise if the atomic spacing is considered to be similar to the bulk metal as the clusters moment will be sensitive to the local geometry and exchange distances. Khanna and Reuse used the local density approximation to calculate that for, Ni 3 , the moment per atom will equal 0.6 µ B and for Ni 5 , 1.6 µ B which is close to an experimental result of 1.8 µ B obtained by Reddy et al [20] and Reuse and Khanna [22] . Khanna et al have also reported that the electronic structure shows band-like behaviour at n = 14 suggesting a similarity to bulk behaviour which is radically different to prior experimental data.…”
Section: Introductionsupporting
confidence: 77%
“…For the case of the 2 K results, the best fit to the data was achieved with a combination of two Langevin functions, which suggests that superparamagnetic nanoparticles are primarily responsible for the paramagnetic response. However, the Langevin function has also been used to describe the low temperature magnetic response of clusters of sub-nanometer scale [20,17,26,27]. The fitting function is given in equation 1, where N is the number of particles per kilogram, µ is the relative magnetic moment, µ B is the Bohr magneton and k B is the Boltzmann constant.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparison with first-principles results serves as a critical justification of our TB parametrization scheme. Figure 3 compares our results with those given by Reddy et al, 10 who, using first-principles molecular-orbital theory, studied the magnetic properties of Ni clusters in most detail. For Ni n with nϭ9 -14, and nϭ19, our spin 's are in perfect agreement with their results.…”
Section: A Size Dependence Of Spin Momentsupporting
confidence: 65%